Specific intracellular signature of SARS-CoV-2 infection using confocal Raman microscopy - Salehi, Hamideh; Ramoji, Anuradha; Mougari, Said; Merida, Peggy; Neyret, Aymeric; Popp, Jürgen; Horvat, Branka; Muriaux, Delphine; Cuisinier, Frederic (Communications Chemistry, 2022)
SARS-CoV-2 infection remains spread worldwide and requires a better understanding of virus-host interactions. Here, we analyzed biochemical modifications due to SARS-CoV-2 infection in cells by confocal Raman microscopy. Obtained results were compared with the infection with another RNA virus, the measles virus. Our results have demonstrated a virus-specific Raman molecular signature, reflecting intracellular modification during each infection. Advanced data analysis has been used to distinguish non-infected versus infected cells for two RNA viruses. Further, classification between non-infected and SARS-CoV-2 and measles virus-infected cells yielded an accuracy of 98.9 and 97.2 respectively, with a significant increase of the essential amino-acid tryptophan in SARS-CoV-2-infected cells. These results present proof of concept for the application of Raman spectroscopy to study virus-host interaction and to identify factors that contribute to the efficient SARS-CoV-2 infection and may thus provide novel insights on viral pathogenesis, targets of therapeutic intervention and development of new COVID-19 biomarkers.
CRIS-Team Scopus Importer:2023-04-20